Does Meconium Peritonitis Pseudo-Cyst Obstruct Labour? - Khalil Al Tawil; Walid Salhi; Safiah Sultan; Mohammad Namshan; Saeed Mohammed (Hindawi Limited, 2012)
Meconium peritonitis pseudo-cyst is very rare. Its perinatal management is controversial and can be associated with increased fetomaternal morbidity and mortality. A 34-week gestation infant with large meconium peritonitis pseudo-cyst, detected by intrapartum fetal ultrasound study, had abnormally increased ratio of fetal abdominal circumference to head circumference. Intrapartum aspiration of the pseudo-cyst was performed and was followed by a smooth vaginal delivery. The postnatal course of the baby showed that early laparotomy was essential for stabilisation of the infant's general condition.